A Comparative And Stylistic Study Of Personification Translation In Literary Texts (Diversity Research: Journal of Analysis and Trends, 2026)
This article analyzes the stylistic features and translation techniques of personification in literary works. Using examples from Wuthering heights and Goldilocks and the Three bears the study shows how personification is used by authors to make texts more vivid and interesting. The research focuses on the methods by Larson to evaluate the preservation of aesthetic and moral value in the target language.